CHOLESTEROL MODULATION OF LIPID PROTEIN INTERACTIONS IN LIVER MICROSOMAL MEMBRANE - A SPIN LABEL STUDY - Castuma, C. E.; Brenner, R. R.; Gattas, Edwil Aparecida de Lucca [UNESP]; Schreier, S.; Lamyfreund, M. T. (Amer Chemical Soc, 1991)
ESR spectra of spin probes were used to monitor lipid-protein interactions in native and cholesterol-enriched microsomal membranes. In both systems composite spectra were obtained, one characteristic of bulk bilayer organization and another due to a motionally restricted population, which was ascribed to lipids in a protein microenvironment. Computer spectral subtractions revealed that cholesterol modulates the order/mobility of both populations in opposite ways, i.e., while the lipid bilayer region gives rise to more anisotropic spectra upon cholesterol enrichment, the spectra of the motionally restricted population become indicative of increased mobility and/or decreased order. These events were evidenced by measurement of both effective order parameters and correlation times. The percentages of the motionally restricted component were invariant in native and cholesterol-enriched microsomes. Variable temperature studies also indicated a lack of variation of the percentages of both spectral components, suggesting that the motionally restricted one was not due to protein aggregation. The results correlate well with the effect of cholesterol enrichment on membrane-bound enzyme kinetics and on the behavior of fluorescent probes [Castuma & Brenner (1986) Biochemistry 25, 4733-4738]. Several hypothesis are put forward to explain the molecular mechanism of the cholesterol-induced spectral changes.